Core-shell fiber composite material and preparation method thereof
Through electrospinning and vacuum suction filtration, uniform and dense double carbon layer composite nanofiber absorbent material was prepared, which solved the problems of the density of existing core-shell fiber materials and the uneven distribution of magnetic metal particles, and achieved improvements in oxidation and wave absorption properties.
Patent Information
- Application Number
- CN202510027434.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-08
- Publication Date
- 2025-04-18
AI Technical Summary
The existing core-shell fiber materials are non-concentrated and continuous, and the magnetic metal particles are unevenly distributed, so the oxidation of magnetic metal wave absorbing materials cannot be completely avoided.
Magnetic metal composite nanofibers are prepared by electrospinning, and vacuum suction filtration and high-temperature carbonization are used to form a uniform and dense double-carbon layer composite nanofiber absorbent material.
The uniform dispersion of magnetic metals within the fiber is achieved, forming an absorbent material with excellent oxidation resistance, and improving the impedance matching characteristics and absorbent properties of the material.
Smart Images

Figure CN119843388A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electromagnetic wave absorbing materials, and in particular relates to a core-shell fiber composite material and a preparation method thereof. Background Art
[0002] The rapid development of 5G communications, electronic products, and space control and measurement technology has brought convenience and safety to human life, but the threat of electromagnetic pollution and exposure of military equipment has also come along. Absorbing materials with excellent performance can reduce electromagnetic pollution, ensure the transmission of signals and the normal operation of precision electronic instruments, and can also improve the anti-detection capability of military equipment to achieve the purpose of stealth. In recent years, although absorbing materials have made great progress, it is still difficult to meet the absorbing performance requirements of "thin, light, wide, and strong" at the same time. At the same time, absorbing materials are easily oxidized at high temperatures and the preparation process is complicated, which limits the further development and application of absorbing materials.
[0003] The anisotropic one-dimensional microstructure has a good promoting effect on the impedance matching characteristics and attenuation characteristics of the absorbing material, especially for nanofibers. The ultra-high aspect ratio can increase the electromagnetic wave attenuation path. The cross structure between the fibers forms a three-dimensional conductive network, which can enhance its own polarization and dielectric loss. The high specific surface area can effectively improve the electromagnetic wave scattering effect. In addition, a large number of gaps between the fibers can also effectively introduce air to adjust the effective dielectric constant and reduce the material density. However, the magnetic metal particles used as absorbents are usually distributed on the surface and inside of the nanofibers, and cannot be completely avoided from being oxidized. At present, the core-shell structure fiber shell obtained by post-processing techniques such as hydrothermal and in-situ polymerization is not dense and continuous, and is unevenly distributed, which cannot completely prevent the entry of oxygen in the environment and its oxidation of magnetic metal absorbing materials. Summary of the invention
[0004] The purpose of the present invention is to provide a method for preparing a core-shell fiber composite material to solve the problems in the prior art that the core-shell fiber material is not dense and continuous, the magnetic metal particles are not evenly distributed, and the oxidation of the magnetic metal absorbing material cannot be completely avoided; A second object of the present invention is to provide a core-shell fiber composite material.
[0005] The technical solution adopted by the present invention is a method for preparing a core-shell fiber composite material, which is specifically carried out according to the following steps: S1, adding a magnetic metal compound and polyacrylonitrile to N,N-dimethylformamide to prepare an electrospinning precursor solution containing a magnetic metal compound; S2, preparing a magnetic metal composite nanofiber membrane using an electrospinning precursor solution containing a magnetic metal compound; S3, proportioning the filtrate, placing the magnetic metal composite nanofiber membrane as a filter membrane in a vacuum filtration device for vacuum filtration to obtain composite nanofibers; S4. Pre-oxidizing and carbonizing the composite nanofibers to obtain a core-shell structure nanofiber microwave absorber.
[0006] Furthermore, the specific process of S1 is as follows: S101, add a magnetic metal compound to N,N-dimethylformamide, and stir at 25-50°C until completely dissolved; S102. Add polyacrylonitrile powder to the solution obtained in S101; stir at 25-50°C for 23-25h.
[0007] Furthermore, in S101, the mass ratio of the magnetic metal compound to N,N-dimethylformamide is (0.385~0.61):10; in S102, the mass ratio of polyacrylonitrile to N,N-dimethylformamide is (0.1:1)~(0.18:1).
[0008] Furthermore, the magnetic compound includes any one or more combinations of ferric acetylacetonate, ferric nitrate, nickel acetylacetonate, cobalt acetylacetonate, and cobalt nitrate.
[0009] Furthermore, the specific process of S2 is as follows: S201, injecting the electrospinning precursor solution into a syringe connected to a 21G stainless steel dispensing needle, and applying a voltage of 12-20 kV for electrospinning; S202, placing the electrospinning product in an oven for drying to obtain a magnetic metal composite nanofiber membrane.
[0010] Furthermore, the ambient temperature of the electrospinning in S201 is 20-30°C, the relative humidity is 30-60%, the receiving plate is aluminum foil, and the receiving distance is 19-21 cm.
[0011] Furthermore, the filtrate is specifically a composition of polyvinyl pyrrolidone, anhydrous ethanol, glacial acetic acid, and tetrabutyl titanate; wherein the molar mass ratio of the magnetic metal compound to tetrabutyl titanate in the electrospinning precursor solution is (0.3:1) to (2.5:1); the amount of glacial acetic acid added is 0.2-2 times the mass of tetrabutyl titanate, the mass fraction of polyvinyl pyrrolidone in the filtrate is 1%-3%; the mass volume ratio of tetrabutyl titanate to anhydrous ethanol is (0.2~1.5) g / 50ml.
[0012] Furthermore, during the vacuum filtration process, the filtrate is added to the filter cup in batches, with the amount of each addition being 5 to 10 ml.
[0013] Furthermore, the process of S4 is specifically as follows: S401, placing the composite nanofiber in a muffle furnace and heating it to 200-250°C in an air atmosphere at a rate of 1-5°C / min for pre-oxidation and maintaining it at this temperature for 1.5-2.5 h, and then cooling it to room temperature with the furnace; S402, after taking out the sample, place it in a tube furnace and heat it to 600-800°C at 1-5°C / min and carbonize it for 1.8-5 h, and cool it to room temperature in the furnace to obtain a core-shell structure nanofiber microwave absorber.
[0014] A core-shell fiber composite material is prepared by the above-mentioned core-shell fiber composite material preparation method.
[0015] The beneficial effects of the present invention are 1. The core-shell fiber shell obtained by post-treatment technologies such as hydrothermal and in-situ polymerization is not dense and continuous, and is unevenly distributed, which cannot completely prevent the entry of oxygen in the environment and its oxidation of magnetic metal absorbers. The present invention obtains nanofibers by electrospinning magnetic metals, vacuum filtration and oxide coating of the nanofibers, and high-temperature carbonization heat treatment to uniformly coat the oxide / carbon on the surface of the magnetic metal / carbon fiber, thereby forming a uniform and dense double-carbon layer composite nanofiber absorbent material.
[0016] 2. In the present invention, electrospinning is to obtain nanofibers by electrostatically stretching the precursor solution and solidifying it. The polymer and magnetic metal salt in the precursor solution are dissolved in the solvent to form a uniform solution. There is no chemical change in the spinning process, so the magnetic metal can be evenly dispersed inside the fiber. At the same time, the electrospun fiber has the structural characteristics of small fiber diameter, small fiber membrane pore size, and high porosity. In the subsequent vacuum filtration process, it can effectively intercept the polymer coils in the filtrate and provide abundant transport channels for the solvent.
[0017] 3. In the present invention, the electrospinning membrane acts as a skeleton carrier, and the filtrate is a mixed solution of semiconductor metal salts and polymers, which is evenly coated on the surface of the spinning fiber after vacuum filtration. Among them, the random coil structure of PVP in the solution and the functional groups carried by the molecules themselves can entrain tetrabutyl titanate when it flows through the fiber, producing effects such as interception, diffusion, inertia, gravity and weak interaction, so that it is efficiently wrapped on the fiber surface to form a shell structure; at the same time, the formation of C / TiO2 after carbonization can avoid direct contact between TiO2 nanoparticles, avoid the formation of stacked mesopores, and allow oxygen to enter. Amorphous carbon plays a role as a medium in the carbonization process, and TiO2 nanoparticles are embedded in amorphous carbon to form a dense shell, which effectively prevents the entry of oxygen and realizes the antioxidant effect of the absorbent.
[0018] 4. The filtrate contains tetrabutyl titanate, which forms TiO2 after high-temperature carbonization. On the one hand, it acts as a polarization loss agent, regulates electromagnetic parameters, and improves impedance matching; on the other hand, it plays the role of protecting the magnetic metal of the core layer.
[0019] 5. The present invention precisely controls the components and content of the composite fiber through the core layer magnetic material and the shell layer oxide, thereby optimizing the impedance matching characteristics of the material, and providing a new efficient, universal, low-cost, and environmentally friendly way to construct an excellent anti-oxidation absorbing material.
[0020] 6. The preparation method of the present invention is simple, the conditions are mild and not harsh, and it is easy to produce on a large scale. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0022] Figure 1 These are the SEM and EDS energy spectra of the Ni / C fiber in comparative example 1 and the Ni / C@TiO2 / C fiber in example 2; wherein, (a) is the SEM image of the Ni / C fiber in comparative example 1; (b) is the EDS energy spectrum of the Ni / C fiber in comparative example 1; (c) is the SEM image of the Ni / C@TiO2 / C fiber in example 2; and (d) is the EDS energy spectrum of the Ni / C@TiO2 / C fiber in example 2.
[0023] Figure 2 is the XRD pattern of Ni / C@TiO2 / C fiber in Example 2; Figure 3 It is the TEM image of Ni / C@TiO2 / C fiber in Example 2 and the Ni, Ti, C, O element mapping image; wherein, (a) is the TEM image of Ni / C@TiO2 / C fiber in Example 2; (b) is the Ni, Ti, C, O element mapping image.
[0024] Figure 4 The graphs are the wave absorption performance of the Ni / C fiber in comparative example 1 and the Ni / C@TiO2 / C fiber in example 2. Among them, (a) is the reflection loss graph of the Ni / C fiber in comparative example 1; (b) is the reflection loss graph of the Ni / C@TiO2 / C fiber in example 2; (c) is the reflection loss graph of the |Z of comparative example 1 and example 2 in / Z0|Spectrum. DETAILED DESCRIPTION
[0025] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0026] The complete steps of this embodiment are as follows: S1: Preparation of electrospinning precursor solution.
[0027] S11: 0.385-0.61 g of a magnetic metal compound is added to 10 g of N,N-dimethylformamide solvent.
[0028] According to the different dissolution temperatures of different magnetic metal compounds, stir at 25-50°C for 30-60 min. The stirring time is determined according to the dissolution properties of the magnetic metal compound to ensure its complete dissolution. Too short a time will result in incomplete dissolution.
[0029] S12: Add (1-1.8) g of polyacrylonitrile (PAN) powder as the matrix for electrospinning. The mass ratio of polyacrylonitrile (PAN) to DMF is: (0.1:1) ~ (0.18:1), and the optimal ratio is (0.15:1). If the mass ratio is too small, the electrospinning precursor solution will be too dilute and the fibers cannot be formed during electrospinning. If the mass ratio is too large, the solution viscosity will be high and the electrospinning needle will be blocked.
[0030] S13: Stir at 25-50℃ for 24 h to obtain electrospinning precursor solution. If the time is too short, the solution will not be completely dissolved and the mixing will be uneven; Among them, the magnetic metal compounds include any one or more of ferric acetylacetonate, ferric nitrate, nickel acetylacetonate, cobalt acetylacetonate, and cobalt nitrate, which play the same role in the material, namely, acting as magnetic loss absorbers, and have the same mechanism of action.
[0031] S2: Perform electrospinning operation.
[0032] S21: Inject the electrospinning precursor solution into a syringe connected to a 21G stainless steel dispensing needle, and apply a voltage of 12-20kV for electrospinning. The electrospinning environment temperature is 20-30°C, the relative humidity is 30-60%, the receiving plate is aluminum foil, and the receiving distance is 19-21cm.
[0033] S22: The received composite product fiber is placed in an oven at 29-31°C and dried for 23.5-24.5 hours to obtain a magnetic metal composite nanofiber membrane.
[0034] S3: Perform suction filtration operation.
[0035] S31: preparing a filtrate, placing the magnetic metal composite nanofiber membrane as a filter membrane in a vacuum filtration device for vacuum filtration. The filtrate is a mixed solution of a binder polyvinyl pyrrolidone (0.5-1.3) g, anhydrous ethanol, glacial acetic acid, and an antioxidant tetrabutyl titanate.
[0036] Among them, the mass of tetrabutyl titanate is 0.2-1.5 g; the molar mass ratio of the magnetic metal compound in the electrospinning precursor solution and the tetrabutyl titanate in the filtrate is controlled to be: 0.3:1~2.5:1; the optimal value is 0.5:1; if the molar ratio is too large, the magnetic metal compound is difficult to dissolve in the solvent, and it will also affect the material properties. If the molar ratio is too small, it will affect the wave absorption performance of the final product.
[0037] The amount of glacial acetic acid added to the filtrate is 0.2-2 times the mass of tetrabutyl titanate, and the preferred amount in this application is 0.5 times. Too much or too little acetic acid will lead to the hydrolysis of tetrabutyl titanate. If the amount of glacial acetic acid added is too much, the acidity of the solution is too strong, which will lead to the excessive hydrolysis of TBT to form TiO2 with larger particles. These particles are difficult to control the size, and will adhere to the surface of the fiber membrane after filtration to form a layered composite membrane structure, affecting the uniformity and performance of the fiber; if the amount of glacial acetic acid added is too little, the acidity of the solution is insufficient, and TBT will start to hydrolyze before filtration and will also form TiO2, whose size cannot be controlled. After filtration, it will adhere to the surface of the fiber membrane to form a layered composite membrane structure, affecting the uniformity and performance of the fiber.
[0038] Take 50ml of anhydrous ethanol.
[0039] The mass fraction of polyvinyl pyrrolidone in the filtrate is 1%-3%. If it is too high, the viscosity of the filtrate will be too high, which will clog the skeleton pores of the electrospun fiber and fail to form a core-shell structure. If it is too low, the coating layer formed is uneven and cannot completely cover the entire fiber. The preferred value in this application is 2%.
[0040] S32: Slowly add the filtrate to the filter cup in batches, with the amount added each time being 5-10 ml. If too little is added each time, the filtrate cannot evenly cover the entire fiber membrane surface; if too much is added, the excessive amount of filtrate will increase the contact time with air, thereby increasing the risk of hydrolysis of tetrabutyl titanate; S33: The filtered fiber membrane is placed in an oven at 29-31°C and dried for 23.5-24.5 hours to obtain magnetic metal / PAN@TiO2 / PVP composite nanofibers.
[0041] S4: Pre-oxidation and carbonization to obtain TiO2 / C coated magnetic metal / C core-shell structure nanofiber microwave absorber.
[0042] S41: The magnetic metal / PAN@TiO2 / PVP composite nanofibers are placed in a muffle furnace and heated to 200-250°C in an air atmosphere at a rate of 1-5°C / min for pre-oxidation to improve the fiber stability, and maintained at this temperature for 1.5-2.5 h, and then cooled to room temperature with the furnace.
[0043] S42: The pre-oxidized sample is then placed in a tube furnace and heated to 600-800°C at 1-5°C / min for carbonization for 1.8-5 h. Too high a temperature will destroy the fiber structure and affect the microwave absorption performance. Too low a temperature will affect the crystallinity and carbonization degree, and also affect the microwave absorption performance. After cooling in the furnace, a core-shell structure nanofiber microwave absorber of TiO2 / C coated with magnetic metal / C is obtained.
[0044] Example 1 S1: Preparation of electrospinning precursor solution.
[0045] S11: Add 0.53 g of iron acetylacetonate powder into 10 g of DMF and stir at 25 °C for 30 min until it is completely dissolved.
[0046] S12: Then 1.5 g PAN was added to the above mixed solution, and the mass ratio of polyacrylonitrile (PAN) to solvent DMF was (0.15:1); S13: Stirring at 25° C. for 24 h to obtain a uniformly mixed electrospinning precursor solution for spinning.
[0047] S2: Perform electrospinning operation.
[0048] S21: The electrospinning precursor solution was injected into a syringe connected to a 21G stainless steel dispensing needle, and a voltage of 16 kV was applied for electrospinning. The electrospinning environment temperature was 20 ° C, the ambient humidity was 30% (relative humidity), the receiving plate was aluminum foil, and the receiving distance was 20 cm.
[0049] S22: The received composite product fiber was placed in an oven at 30°C and dried for 24 h to obtain a Fe / PAN composite nanofiber membrane.
[0050] S3: Perform suction filtration operation.
[0051] S31: The Fe / PAN composite nanofiber membrane is placed as a filter membrane in a vacuum filtration device for vacuum filtration. The filtrate is a mixed solution of PVP, anhydrous ethanol, glacial acetic acid and tetrabutyl titanate.
[0052] Among them, 1.0g of tetrabutyl titanate; the molar mass ratio of the magnetic metal compound to tetrabutyl titanate is: 0.5:1 The amount of glacial acetic acid added is 0.5 times the mass of tetrabutyl titanate, and 0.5 g of glacial acetic acid is taken; 50ml of anhydrous ethanol; The mass of polyvinyl pyrrolidone is 1g; the mass fraction of polyvinyl pyrrolidone in the filtrate is: 2% S32: Pour the filtrate into the filter cup several times, about 5 mL each time.
[0053] S33: The filtered fiber membrane was placed in a 30°C oven and dried for 24 h to obtain Fe / PAN@TiO2 / PVP composite nanofibers.
[0054] S4: Obtain TiO2 / C coated magnetic metal / C core-shell structure nanofiber microwave absorber.
[0055] S41: The Fe / PAN@TiO2 / PVP composite nanofibers were placed in a muffle furnace and heated to 230°C in an air atmosphere at a rate of 2°C / min for pre-oxidation stabilization for 2.0 h, and then cooled in the furnace.
[0056] S42: The pre-oxidized sample was then placed in a tubular furnace and heated to 800°C at 5°C / min for carbonization for 3 h, followed by cooling in the furnace to obtain a Fe / C@TiO2 / C core-shell structured nanofiber microwave absorber.
[0057] Example 2 S1: Preparation of electrospinning precursor solution.
[0058] S11: Add 0.385 g nickel acetylacetonate powder into 10 g DMF and stir at 50 °C for 60 min until it is completely dissolved.
[0059] S12: Then 1.5 g PAN is added to the mixed solution. The mass ratio of polyacrylonitrile (PAN) to solvent DMF is (0.15:1).
[0060] S13: Stir at 50°C for 24 h to obtain a uniformly mixed electrospinning precursor solution for spinning.
[0061] S2: Perform electrospinning operation.
[0062] S21: The electrospinning precursor solution was injected into a syringe connected to a 21G stainless steel dispensing needle, and a voltage of 14 kV was applied for electrospinning. The electrospinning environment temperature was 25°C, the ambient humidity was 50% (relative humidity), the receiving plate was aluminum foil, and the receiving distance was 20 cm.
[0063] S22: The received composite product fiber was placed in an oven at 30°C and dried for 24 h to obtain a Ni / PAN composite nanofiber membrane.
[0064] S3: Perform suction filtration operation.
[0065] S31: Place the Ni / PAN composite nanofiber membrane as a filter membrane in a vacuum filtration device for vacuum filtration. The filtrate is a mixed solution of PVP, anhydrous ethanol, glacial acetic acid and tetrabutyl titanate. The mass of tetrabutyl titanate is 1 g; the molar mass ratio of the magnetic metal compound to tetrabutyl titanate is 0.5:1; The amount of glacial acetic acid added to the filtrate is 0.5 times the mass of tetrabutyl titanate. Take 0.5g of glacial acetic acid. Anhydrous ethanol is 50 mL; The mass of polyvinyl pyrrolidone is 1g, and the mass fraction of polyvinyl pyrrolidone in the filtrate is 2%; S32: Pour the filtrate into the filter cup, about 5 mL at a time.
[0066] S33: The filtered fiber membrane was placed in an oven at 30 °C and dried for 24 h to obtain Ni / PAN@TiO2 / PVP composite nanofibers.
[0067] S4: Obtain TiO2 / C coated magnetic metal / C core-shell structure nanofiber microwave absorber.
[0068] S41: The Ni / PAN@TiO2 / PVP composite nanofibers were placed in a muffle furnace and heated to 230°C in an air atmosphere at a rate of 2°C / min for pre-oxidation stabilization for 2.0 h, and then cooled in the furnace.
[0069] S42: The pre-oxidized sample was then placed in a tubular furnace and heated to 700°C at 2°C / min for carbonization for 2 h, and then cooled in the furnace to obtain a Ni / C@TiO2 / C core-shell structured nanofiber microwave absorber.
[0070] Example 3 S1: Preparation of electrospinning precursor solution.
[0071] S11: Add 0.388 g of cobalt acetylacetonate powder to 10 g of DMF and stir at 25 °C for 60 min until all the powder is dissolved.
[0072] S12: Then 1.5 g PAN is added to the above mixed solution, and the mass ratio of polyacrylonitrile (PAN) to solvent DMF is (0.15:1); S13: Stir at 25°C for 25 h to obtain a uniformly mixed electrospinning precursor solution for spinning.
[0073] S2: Perform electrospinning operation.
[0074] S21: The electrospinning precursor solution was injected into a syringe connected to a 21G stainless steel dispensing needle, and a voltage of 14 kV was applied for electrospinning. The electrospinning environment temperature was 25°C, the ambient humidity was 50% (relative humidity), the receiving plate was aluminum foil, and the receiving distance was 20 cm.
[0075] S22: The received composite product fiber was placed in an oven at 30°C and dried for 24 h to obtain a Co / PAN composite nanofiber membrane.
[0076] S3: Perform suction filtration operation.
[0077] S31: Place the Co / PAN composite nanofiber membrane as a filter membrane in a vacuum filtration device for vacuum filtration. The filtrate is a mixed solution of PVP, anhydrous ethanol, glacial acetic acid and tetrabutyl titanate. The mass of tetrabutyl titanate is 1 g; the molar mass ratio of the magnetic metal compound to tetrabutyl titanate is 0.5:1; The amount of glacial acetic acid added to the filtrate is 0.5 times the mass of tetrabutyl titanate. Take 0.5g of glacial acetic acid. Take 50ml of anhydrous ethanol; The mass of polyvinyl pyrrolidone is 1g, and the mass fraction of polyvinyl pyrrolidone in the filtrate is 2%; S32: Pour the filtrate into the filter cup, about 5 mL at a time.
[0078] S33: The filtered fiber membrane was placed in an oven at 30 °C and dried for 24 h to obtain Co / PAN@TiO2 / PVP composite nanofibers.
[0079] S4: Obtain TiO2 / C coated magnetic metal / C core-shell structure nanofiber microwave absorber.
[0080] S41: The Co / PAN@TiO2 / PVP composite nanofibers were placed in a muffle furnace and heated to 230°C in an air atmosphere at a rate of 2°C / min for pre-oxidation stabilization for 2.0 h, and then cooled in the furnace.
[0081] S42: The pre-oxidized sample was then placed in a tubular furnace and heated to 700°C at 2°C / min for carbonization for 2 h, followed by cooling in the furnace to obtain a Co / C@TiO2 / C core-shell structured nanofiber microwave absorber.
[0082] Example 4 S1: Preparation of electrospinning precursor solution.
[0083] S11: Add 0.40 g of ferric acetylacetonate and 0.15 g of cobalt acetylacetonate powder to 10 g of DMF and continue stirring at 25 °C for 60 min until all the powders are dissolved.
[0084] S12: Then 1.5 g PAN was added to the above mixed solution, and the mass ratio of polyacrylonitrile (PAN) to solvent DMF was (0.15:1); S13: Stir at 25°C for 24 h to obtain a uniformly mixed electrospinning precursor solution for spinning.
[0085] S2: Perform electrospinning operation.
[0086] S21: The electrospinning precursor solution was injected into a syringe connected to a 21G stainless steel dispensing needle, and a voltage of 14 kV was applied for electrospinning. The electrospinning environment temperature was 25°C, the ambient humidity was 50% (relative humidity), the receiving plate was aluminum foil, and the receiving distance was 20 cm.
[0087] S22: The received composite product fiber was placed in an oven at 30°C and dried for 24 h to obtain a FeCo / PAN composite nanofiber membrane.
[0088] S3: Perform suction filtration operation.
[0089] S31: Place the FeCo / PAN composite nanofiber membrane as a filter membrane in a vacuum filtration device for vacuum filtration. The filtrate is a mixed solution of PVP, anhydrous ethanol, glacial acetic acid and tetrabutyl titanate. The mass of tetrabutyl titanate is 1.2 g; The amount of glacial acetic acid added is 0.5 times the mass of tetrabutyl titanate. Take 0.6g of glacial acetic acid, and the molar mass ratio of the magnetic metal compound to tetrabutyl titanate is: 0.5:1 Anhydrous ethanol is 50 mL; Polyvinyl pyrrolidone and 1g, the mass fraction of polyvinyl pyrrolidone in the filtrate is: 2%, S32: Pour the filtrate into the filter cup, about 8 mL each time.
[0090] S33: The filtered fiber membrane was placed in an oven at 30 °C and dried for 24 h to obtain FeCo / PAN@TiO2 / PVP composite nanofibers.
[0091] S4: Obtain TiO2 / C coated magnetic metal / C core-shell structure nanofiber microwave absorber.
[0092] S41: The FeCo / PAN@TiO2 / PVP composite nanofibers were placed in a muffle furnace and heated to 230°C in an air atmosphere at a rate of 2°C / min for pre-oxidation stabilization for 2.0 h, and then cooled in the furnace.
[0093] S42: The pre-oxidized sample was then placed in a tubular furnace and heated to 700°C at 5°C / min for carbonization for 2 h, and then cooled in the furnace to obtain a FeCo / C@TiO2 / C core-shell structured nanofiber microwave absorber.
[0094] Example 5 The difference from Example 1 is: In S1, the magnetic metal compound is iron nitrate, and its mass is 0.61 g.
[0095] Example 6 The difference from Example 3 is: In S1, the magnetic metal compound is cobalt nitrate, with a mass of 0.44 g; Example 7 S1: Preparation of electrospinning precursor solution.
[0096] S11: Add 0.385 g nickel acetylacetonate powder into 10 g DMF and stir at 50 °C for 60 min until it is completely dissolved.
[0097] S12: Then add 1 g PAN to the above mixed solution. The mass ratio of polyacrylonitrile (PAN) to solvent DMF is: (0.1:1); S13: Stirring at 50°C for 24 h to obtain a uniformly mixed electrospinning precursor solution for spinning.
[0098] S2: Perform electrospinning operation.
[0099] S21: The electrospinning precursor solution was injected into a syringe connected to a 21G stainless steel dispensing needle, and a voltage of 12 kV was applied for electrospinning. The electrospinning environment temperature was 20°C, the environment humidity was 30% (relative humidity), the receiving plate was aluminum foil, and the receiving distance was 19 cm.
[0100] S22: The received composite product fiber was placed in an oven at 29°C and dried for 24.5 h to obtain a Ni / PAN composite nanofiber membrane.
[0101] S3: Perform suction filtration operation.
[0102] S31: Place the Ni / PAN composite nanofiber membrane as a filter membrane in a vacuum filtration device for vacuum filtration. The filtrate is a mixed solution of PVP, anhydrous ethanol, glacial acetic acid and tetrabutyl titanate. The mass of tetrabutyl titanate is 1.5 g; the molar mass ratio of the magnetic metal compound to tetrabutyl titanate is 0.3:1; The amount of glacial acetic acid added to the filtrate is 0.2 times the mass of tetrabutyl titanate; Anhydrous ethanol is 50mL; The mass of polyvinyl pyrrolidone is 0.5 g, and the mass fraction of polyvinyl pyrrolidone is 1%; S32: Pour the filtrate into the filter cup several times, about 5 mL each time.
[0103] S33: The filtered fiber membrane was placed in an oven at 30 °C and dried for 24 h to obtain Ni / PAN@TiO2 / PVP composite nanofibers.
[0104] S4: Obtain TiO2 / C coated magnetic metal / C core-shell structure nanofiber microwave absorber.
[0105] S41: The Ni / PAN@TiO2 / PVP composite nanofibers were placed in a muffle furnace and heated to 200°C in an air atmosphere at a rate of 1°C / min for pre-oxidation and stabilization for 2.5 hours, and then cooled in the furnace.
[0106] S42: The pre-oxidized sample is then placed in a tubular furnace and heated to 600°C at 1°C / min for carbonization for 5 hours, and then cooled in the furnace to obtain a Ni / C@TiO2 / C core-shell structure nanofiber microwave absorber.
[0107] Example 8 S1: Preparation of electrospinning precursor solution.
[0108] S11: Add 0.385 g nickel acetylacetonate powder into 10 g DMF and stir at 50 °C for 60 min until it is completely dissolved.
[0109] S12: Then add 1.8g PAN to the above mixed solution. The mass ratio of polyacrylonitrile (PAN) to solvent DMF is: (0.18:1); S13: Stirring at 50°C for 24 h to obtain a uniformly mixed electrospinning precursor solution for spinning.
[0110] S2: Perform electrospinning operation.
[0111] S21: The electrospinning precursor solution was injected into a syringe connected to a 21G stainless steel dispensing needle, and a voltage of 20 kV was applied for electrospinning. The electrospinning environment temperature was 30 ° C, the ambient humidity was 60% (relative humidity), the receiving plate was aluminum foil, and the receiving distance was 21 cm.
[0112] S22: The received composite product fiber was placed in an oven at 31°C and dried for 23.5 h to obtain a Ni / PAN composite nanofiber membrane.
[0113] S3: Perform suction filtration operation.
[0114] S31: Place the Ni / PAN composite nanofiber membrane as a filter membrane in a vacuum filtration device for vacuum filtration. The filtrate is a mixed solution of PVP, anhydrous ethanol, glacial acetic acid and tetrabutyl titanate. The mass of tetrabutyl titanate is 0.2 g, and the molar mass ratio of the magnetic metal compound to tetrabutyl titanate is 2.5:1; The amount of glacial acetic acid added to the filtrate is twice the mass of tetrabutyl titanate; Take 50 ml of anhydrous ethanol; The mass of polyvinyl pyrrolidone is 1.3 g, and the mass fraction of polyvinyl pyrrolidone in the filtrate is 3%.
[0115] S32: Pour the filtrate into the filter cup several times, about 10 mL each time.
[0116] S33: The filtered fiber membrane was placed in an oven at 30 °C and dried for 24 h to obtain Ni / PAN@TiO2 / PVP composite nanofibers.
[0117] S4: Obtain TiO2 / C coated magnetic metal / C core-shell structure nanofiber microwave absorber.
[0118] S41: The Ni / PAN@TiO2 / PVP composite nanofibers were placed in a muffle furnace and heated to 250°C in an air atmosphere at a rate of 5°C / min for pre-oxidation and stabilization for 1.5 h, and then cooled in the furnace.
[0119] S42: The pre-oxidized sample was then placed in a tubular furnace and heated to 800°C at 5°C / min for carbonization for 2 h, and then cooled in the furnace to obtain a Ni / C@TiO2 / C core-shell structured nanofiber microwave absorber.
[0120] Comparative Example 1 S1: Preparation of electrospinning precursor solution.
[0121] S11: Add 0.385 g nickel acetylacetonate powder into 10 g DMF and stir at 50 °C for 60 min until it is completely dissolved.
[0122] S12: Then add 1.5 g PAN into the above mixed solution.
[0123] S13: Stir at 50°C for 24 h to obtain a uniformly mixed electrospinning precursor solution for spinning.
[0124] S2: Perform electrospinning operation.
[0125] S21: The electrospinning precursor solution was injected into a syringe connected to a 21G stainless steel dispensing needle, and a voltage of 12 kV was applied for electrospinning. The electrospinning environment temperature was 25 ° C, the ambient humidity was 50% (relative humidity), the receiving plate was aluminum foil, and the receiving distance was 20 cm.
[0126] S22: The received composite product fiber was placed in an oven at 30°C and dried for 24 h to obtain a Ni / PAN composite nanofiber membrane.
[0127] S3: Obtain Ni / C nanofibers.
[0128] S31: The Ni / PAN composite nanofibers were placed in a muffle furnace and heated to 230°C in an air atmosphere at a rate of 2°C / min for pre-oxidation and stabilization for 2.0 h, and then cooled in the furnace.
[0129] S32: The pre-oxidized sample was then placed in a tubular furnace and heated to 700°C at 2°C / min for carbonization for 2 h, and then cooled in the furnace to obtain Ni / C nanofibers.
[0130] Comparative Example 2 S1: Preparation of electrospinning precursor solution.
[0131] S11: Add 0.385 g nickel acetylacetonate powder into 10 g DMF and stir at 50 °C for 60 min until it is completely dissolved.
[0132] S12: Then 1.5 g PAN is added to the mixed solution. The mass ratio of polyacrylonitrile (PAN) to solvent DMF is (0.15:1).
[0133] S13: Stir at 50°C for 24 h to obtain a uniformly mixed electrospinning precursor solution for spinning.
[0134] S2: Perform electrospinning operation.
[0135] S21: The electrospinning precursor solution was injected into a syringe connected to a 21G stainless steel dispensing needle, and a voltage of 12 kV was applied for electrospinning. The electrospinning environment temperature was 25 ° C, the ambient humidity was 50% (relative humidity), the receiving plate was aluminum foil, and the receiving distance was 20 cm.
[0136] S22: The received composite product fiber was placed in an oven at 30°C and dried for 24 h to obtain a Ni / PAN composite nanofiber membrane.
[0137] S3: Perform suction filtration operation.
[0138] S31: Place the Ni / PAN composite nanofiber membrane as a filter membrane in a vacuum filtration device for vacuum filtration. The filtrate is a mixed solution of PVP, anhydrous ethanol, and glacial acetic acid. Take 0.5 g of glacial acetic acid and 50 mL of anhydrous ethanol; The mass of polyvinyl pyrrolidone is 1 g, and the mass fraction of polyvinyl pyrrolidone in the filtrate is 2%; S32: Pour the filtrate into the filter cup, about 5 mL at a time.
[0139] S33: The filtered fiber membrane was placed in an oven at 30 °C and dried for 24 h to obtain Ni / PAN@PVP composite nanofibers.
[0140] S4: Obtain a C-coated magnetic metal / C core-shell structure nanofiber microwave absorber.
[0141] S41: The Ni / PAN@PVP composite nanofibers were placed in a muffle furnace and heated to 230°C in an air atmosphere at a rate of 2°C / min for pre-oxidation stabilization for 2.0 h, and then cooled in the furnace.
[0142] S42: The pre-oxidized sample was then placed in a tube furnace and heated to 700°C at 2°C / min for carbonization for 2 h, and then cooled in the furnace to obtain a Ni / C@C core-shell structured nanofiber microwave absorber.
[0143] Tetrabutyl titanate was not added to the filtrate, so the obtained Ni / C@C nanofibers lacked the polarization loss absorber TiO2 and could not effectively reduce the conductivity, resulting in a single loss mechanism, poor impedance matching, and reduced absorbing performance.
[0144] Comparative Example 3 S1: Preparation of electrospinning precursor solution.
[0145] S11: Add 0.385 g nickel acetylacetonate powder into 10 g DMF and stir at 50 °C for 60 min until it is completely dissolved.
[0146] S12: Then 1.5 g PAN is added to the mixed solution. The mass ratio of polyacrylonitrile (PAN) to solvent DMF is (0.15:1).
[0147] S13: Stir at 50°C for 24 h to obtain a uniformly mixed electrospinning precursor solution for spinning.
[0148] S2: Perform electrospinning operation.
[0149] S21: The electrospinning precursor solution was injected into a syringe connected to a 21G stainless steel dispensing needle, and a voltage of 12 kV was applied for electrospinning. The electrospinning environment temperature was 25 ° C, the ambient humidity was 50% (relative humidity), the receiving plate was aluminum foil, and the receiving distance was 20 cm.
[0150] S22: The received composite product fiber was placed in an oven at 30°C and dried for 24 h to obtain a Ni / PAN composite nanofiber membrane.
[0151] S3: Perform suction filtration operation.
[0152] S31: Place the Ni / PAN composite nanofiber membrane as a filter membrane in a vacuum filtration device for vacuum filtration. The filtrate is a mixed solution of anhydrous ethanol, tetrabutyl titanate, and glacial acetic acid. The mass of tetrabutyl titanate is 1 g; the molar mass ratio of the magnetic metal compound to tetrabutyl titanate is 0.5:1; The amount of glacial acetic acid added to the filtrate is 0.5 times the mass of tetrabutyl titanate. Take 0.5g of glacial acetic acid. Anhydrous ethanol is 50 mL; S32: Pour the filtrate into the filter cup, about 5 mL at a time.
[0153] S33: The filtered fiber membrane was placed in an oven at 30°C and dried for 24 h to obtain Ni / PAN / TiO2 composite nanofibers.
[0154] S4: Obtain Ni / C / TiO2 nanofiber microwave absorber.
[0155] S41: The Ni / PAN / TiO2 composite nanofibers were placed in a muffle furnace and heated to 230°C in an air atmosphere at a rate of 2°C / min for pre-oxidation and stabilization for 2.0 h, and then cooled in the furnace.
[0156] S42: The pre-oxidized sample was then placed in a tubular furnace and heated to 700°C at 2°C / min for carbonization for 2 h, and then cooled in the furnace to obtain a Ni / C / TiO2 nanofiber microwave absorber.
[0157] Polyvinyl pyrrolidone was not added to the filtrate, and most of the small molecule solution formed entered the filtration bottle through the skeleton holes between the fibers during the filtration process. A small amount of tetrabutyl titanate was adsorbed on the fiber surface, and a complete and uniform core-shell structure fiber could not be obtained.
[0158] Figure 1In (c), the SEM image of Ni / C@TiO2 / C fiber prepared in Example 2 is shown, and the inset is the corresponding diameter distribution bar graph, which shows that the fiber surface is smooth, the diameter distribution is uniform, and the average diameter is 0.40 μm. In (d), the selected area EDS spectrum analysis shows that the surface of C / Ni@C / TiO2 fiber contains titanium. Figure 1 In (a) and (b), the comparison of the SEM image of the Ni / C fiber prepared in Comparative Example 1 and its diameter distribution bar graph shows that the fiber morphology does not change significantly after vacuum filtration and coating of the TiO2 / C shell layer in Example 2, and the average diameter increases from 0.38 μm to 0.40 μm, forming a coating layer with an average thickness of 20 nm. Combined with the comparison of selected area EDS spectrum analysis, it can be determined that the vacuum filtration technology can successfully coat the TiO2 / C shell layer on the Ni / C fiber to form a core-shell structure.
[0159] Figure 2 The XRD pattern of Ni / C@TiO2 / C fiber prepared in Example 2 shows that Ni / C@TiO2 / C fiber is composed of amorphous carbon, TiO2 and metallic nickel. o The broad peak in the range originates from amorphous carbon from polymer pyrolysis. o , 51.6 o and 76.2 o The characteristic peaks at 25.4 correspond to the (111), (200) and (220) crystal planes of nickel (JCPDF No.04-0850). o , 37.7 o , 48.0 o and 62.7 o The characteristic peaks at 27.4 o , 36.0°, 41.2°, 54.2 o and 69.0 o The characteristic peaks at 370 nm correspond to the (110), (101), (111), (211) and (301) crystal planes of rutile titanium dioxide (R-TiO2, JCPDF No.21-1276). No impurity phase was found in XRD, which further proved the successful preparation and high purity of Ni / C@TiO2 / C composite fibers.
[0160] Figure 3The SEM and corresponding element mapping images of the Ni / C@TiO2 / C fiber prepared in Example 2. In (a), the prepared Ni / C@TiO2 / C fiber has an obvious core-shell structure, and from (b) it can be seen that the four elements C, N0i, Ti, and O are evenly distributed in the entire fiber, further proving that the fiber obtained in Example 2 has a core-shell structure and the TiO2 / C shell layer is successfully coated on the Ni / C fiber core.
[0161] Figure 4 The graphs are the wave absorption performance of the Ni / C fiber in comparative example 1 and the Ni / C@TiO2 / C fiber in example 2. Among them, (a) is the reflection loss graph of the Ni / C fiber in comparative example 1; (b) is the reflection loss graph of the Ni / C@TiO2 / C fiber in example 2; (c) is the reflection loss graph of the |Z of comparative example 1 and example 2 in / Z0|Spectrum.
[0162] Depend on Figure 4 As shown in (a) and (b), for Ni / C fiber, the best absorption performance is when the thickness is 2.0 mm, the minimum RL value is -14.0 dB, and the effective absorption bandwidth (RL<-10 dB) is 3.5 GHz (9.9-13.4 GHz). For Ni / C@TiO2 / C fiber, when the thickness is 3.0 mm, the minimum RL value reaches -48.5 dB at 12.3 GHz; at a thickness of 2.7 mm, the effective absorption band (RL<-10 dB) is as wide as 6.8 GHz (11.2-18.0 GHz). The absorption performance is significantly improved.
[0163] Depend on Figure 4 (c) It can be seen that in Example 2, |Z in The value of / Z0| is close to 1 in a wide frequency band. At 9.6 and 13.7 GHz, |Z in The value of / Z0| is 1, indicating that the absorber has an ideal impedance match with free space, while in Comparative Example 1, |Z in The value of / Z0| is relatively far from 1, which indicates that Ni / C@TiO2 / C fiber has better impedance matching.
[0164] Table 1 Test results of the wave absorption performance of the core-shell fiber composite materials prepared in Examples 1, 3, 4, 7, 8, Comparative Examples 2 and 3
[0165] As can be seen from Table 1, Examples 1-4 all show good wave absorbing performance, that is, they have a larger effective absorption bandwidth at a lower thickness. In comparison, the absorption intensity of Example 1 is weaker. Although the saturation magnetic susceptibility of Fe is higher, Fe3C impurities may be generated in carbon reduction. Secondly, the electrical conductivity of iron is relatively low, and the electrical conductivity loss is small, resulting in a decrease in wave absorbing performance. The wave absorbing performance of Examples 3 and 4 is slightly different from that of Example 2, and the absorption intensity and effective absorption bandwidth are slightly smaller. This may be due to the high electrical conductivity of metal cobalt, resulting in relatively poor impedance matching. Implementations 7 and 8 show poor wave absorbing performance, wherein Example 7 contains excessive oxide semiconductor TiO2, and the electrical conductivity is severely reduced, which will lead to impedance mismatch, while affecting the electrical conductivity loss and reducing the wave absorbing performance. Implementation 8 contains less TiO2, and due to the high mass fraction of PVP in the filtrate and the high carbon content after high-temperature carbonization, the absorbent has a higher electrical conductivity. Although the attenuation capacity can be improved, it will also destroy the impedance matching characteristics and hinder electromagnetic waves from entering the absorber. Comparative Examples 2 and 3 have poor absorbing performance due to the lack of polarization loss absorber or complete core-shell structure.
[0166] Each embodiment in this specification is described in a related manner, and the same or similar parts between the embodiments can be referred to each other, and each embodiment focuses on the differences from other embodiments. In particular, for the system embodiment, since it is basically similar to the method embodiment, the description is relatively simple, and the relevant parts can be referred to the partial description of the method embodiment.
[0167] The above description is only a preferred embodiment of the present invention and is not intended to limit the protection scope of the present invention. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention are included in the protection scope of the present invention.
Claims
1. A method for preparing a core-shell fiber composite material, characterized in that: Follow these steps: S1, adding a magnetic metal compound and polyacrylonitrile to N,N-dimethylformamide to prepare an electrospinning precursor solution containing a magnetic metal compound; S2, preparing a magnetic metal composite nanofiber membrane using an electrospinning precursor solution containing a magnetic metal compound; S3, proportioning the filtrate, placing the magnetic metal composite nanofiber membrane as a filter membrane in a vacuum filtration device for vacuum filtration to obtain composite nanofibers; S4. Pre-oxidizing and carbonizing the composite nanofibers to obtain a core-shell structure nanofiber microwave absorber.
2. The method for preparing a core-shell fiber composite material according to claim 1, characterized in that: The specific process of S1 is as follows: S101, add a magnetic metal compound to N,N-dimethylformamide, and stir at 25-50°C until completely dissolved; S102. Add polyacrylonitrile powder to the solution obtained in S101; stir at 25-50°C for 23-25h.
3. The method for preparing a core-shell fiber composite material according to claim 2, characterized in that: In the S101, the mass ratio of the magnetic metal compound to N,N-dimethylformamide is (0.385~0.61):10; in the S102, the mass ratio of polyacrylonitrile to N,N-dimethylformamide is (0.1:1)~(0.18:1).
4. The method for preparing a core-shell fiber composite material according to claim 2, characterized in that: The magnetic compound includes any one or more combinations of iron acetylacetonate, iron nitrate, nickel acetylacetonate, cobalt acetylacetonate and cobalt nitrate.
5. The method for preparing a core-shell fiber composite material according to claim 1, characterized in that: The specific process of S2 is as follows: S201, injecting the electrospinning precursor solution into a syringe connected to a 21G stainless steel dispensing needle, and applying a voltage of 12-20 kV for electrospinning; S202, placing the electrospinning product in an oven for drying to obtain a magnetic metal composite nanofiber membrane.
6. The method for preparing a core-shell fiber composite material according to claim 5, characterized in that: The ambient temperature of the electrospinning in S201 is 20-30°C, the relative humidity is 30-60%, the receiving plate is aluminum foil, and the receiving distance is 19-21 cm.
7. The method for preparing a core-shell fiber composite material according to claim 1, characterized in that: The filtrate is specifically a composition of polyvinyl pyrrolidone, anhydrous ethanol, glacial acetic acid, and tetrabutyl titanate; wherein the molar mass ratio of the magnetic metal compound to tetrabutyl titanate in the electrospinning precursor solution is (0.3:1) to (2.5:1); the amount of glacial acetic acid added is 0.2-2 times the mass of tetrabutyl titanate, the mass fraction of polyvinyl pyrrolidone in the filtrate is 1%-3%; the mass volume ratio of tetrabutyl titanate to anhydrous ethanol is (0.2~1.5) g / 50 ml.
8. The method for preparing a core-shell fiber composite material according to claim 1, characterized in that: During the vacuum filtration process, the filtrate is added to the filter cup in batches, with the amount of each addition being 5 to 10 ml.
9. The method for preparing a core-shell fiber composite material according to claim 1, characterized in that: The process of S4 is specifically as follows: S401, placing the composite nanofiber in a muffle furnace and heating it to 200-250°C in an air atmosphere at a rate of 1-5°C / min for pre-oxidation and maintaining it at this temperature for 1.5-2.5 h, and then cooling it to room temperature with the furnace; S402, after taking out the sample, place it in a tube furnace and heat it to 600-800°C at 1-5°C / min and carbonize it for 1.8-5 h, and cool it to room temperature in the furnace to obtain a core-shell structure nanofiber microwave absorber.
10. A core-shell fiber composite material, prepared by the method for preparing a core-shell fiber composite material according to any one of claims 1 to 9.